National sport organisation responses to independent reviews. Issue 1 (2nd January 2021) - Dawbin, Timothy M.; Sam, Michael P.; Stenling, Cecilia
ABSTRACT: Government sport agencies maintain an enduring interest in National Sport Organisations (NSOs) and deploy a number of tools to make them more effective and efficient. Independent, consultant-led reviews are increasingly used to assess aspects of capability, sustainability, governance, management, and programme delivery. However, it is unknown how NSOs respond to these instruments and the latter's capacity to induce substantive change. This research investigates how and why NSOs respond to independent reviews of their organisations, whether purposefully, passively or politically. Drawing from documents and interviews with NSO officials, findings demonstrate that NSOs respond both purposefully and passively to recommendations advising centralised control over their networks. While there is evidence that responses to reviews invite further state involvement, the mix of responses, along with the finding that 'reviews beget reviews', suggests NSOs maintain considerable agency to 'muddle through' recommendations. This study speaks to why reviews may be repeated and why they may face increasing scepticism.